Implementing circular economy and sustainability policies in Rwanda: Experiences of Rwandan manufacturers with the plastic ban policy - Ogutu, Moses Onyango; Akor, Jackson; Mulindwa, Mike Ssempa; Heshima, Olexa; Nsengimana, Christian (Frontiers in Sustainability, 2023)
Countries around the world are increasingly adopting mitigation strategies in response to the environmental damage caused by plastic waste. The most widely used approach has been to encourage the adoption of environment-friendly alternatives, banning single-use plastics, and implementing circular economy (CE) principles. Since banning plastics in 2005, Rwanda has consistently implemented policies that balance national growth and environmental conservation while using the plastic ban as an enforcement strategy. Despite the rise of plastic waste regulation and trends in the adoption of CE policies globally, investigations of their impact on businesses remain limited. Research on adoption of CE policies in Africa is particularly limited despite African countries leading the uptake of plastic ban laws and CE-related policies. This paper examines how the 10-R principles of CE feature in Rwanda’s sustainability policies. The paper also provides the experiences of Rwandan manufacturers following the implementation of the plastic ban and CE policies. A review of 11 environmental sustainability policies shows alignment to different levels of 10-R principles of the circular economy. Meanwhile, field interviews with leading manufacturers comprising producers (primary manufacturers) and users (secondary manufacturers) of single-use plastic in Rwanda indicate that businesses have faced internal and external challenges in complying with the plastic ban. These challenges range from limited capital to acquire new industrial technology, lack of expertise on developing circular business models, lack of alternative packaging to plastics to loss in regional competition since Rwanda’s competitors in the international market still use cheap plastic packaging. The results suggest that tackling environmental challenges caused by plastic waste and implementing CE and other green policies require collaboration between governments regarding regulation, innovation from businesses, and individual action. The results also indicate that insufficient government support, such as lack of finance and capacity development to develop new business models, ambiguous regulatory framework, and inadequate stakeholder consultations, impedes business uptake of CE policies. Finally, the paper argues that the special exemption permit that allows companies to continue importing or using plastics inhibits Rwandan firms from exploring or innovating alternative packaging to replace plastics.